Numerical Study of Surfactant-Laden Drop-Drop Interactions (Communications in Computational Physics, 2011)
In this paper, we numerically investigate the effects of surfactant on drop-dropinteractions in a 2D shear flow using a coupled level-set and immersed interfaceapproach proposed in (Xu et al., J. Comput. Phys., 212 (2006), 590–616). We find thatsurfactant plays a critical and nontrivial role in drop-drop interactions. In particular,we find that the minimum distance between the drops is a non-monotone function ofthe surfactant coverage and Capillary number. This non-monotonic behavior, whichdoes not occur for clean drops, is found to be due to the presence of Marangoni forcesalong the drop interfaces. This suggests that there are non-monotonic conditions forcoalescence of surfactant-laden drops, as observed in recent experiments of Leal andco-workers. Although our study is two-dimensional, we believe that drop-drop interactionsin three-dimensional flows should be qualitatively similar as the Maragoniforces in the near contact region in 3D should have a similar effect.